2023
DOI: 10.1590/1982-0224-2022-0103
|View full text |Cite
|
Sign up to set email alerts
|

Fish functional trophic groups in headwater karst streams from the Upper Paraguay River basin

Francisco Severo-Neto,
Gabriel L. Brejão,
Lilian Casatti

Abstract: Data obtained by direct observation of organisms in their natural habitats can provide valuable contributions regarding intra- and inter-specific interactions, as well as spatial distribution and trophic relationships. However, relatively few such data are available for the Neotropical ichthyofauna relative to the great species diversity of this region. We present data on the ichthyofauna in karst environments of the Serra da Bodoquena, Upper Paraguay River basin regarding their categorization into functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Bryconamericus exodon is usually categorized as insectivorous (Russo et al, 2004;Novakowski et al, 2008), and our data corroborate this classification. Other studies found this species to be predominantly diurnal, occurring mainly in the littoral portion and primarily feeding on autochthonous prey or drifting terrestrial insects (Severo-Neto et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…Bryconamericus exodon is usually categorized as insectivorous (Russo et al, 2004;Novakowski et al, 2008), and our data corroborate this classification. Other studies found this species to be predominantly diurnal, occurring mainly in the littoral portion and primarily feeding on autochthonous prey or drifting terrestrial insects (Severo-Neto et al, 2023).…”
Section: Discussionmentioning
confidence: 95%